20‐2: High Efficiency and Long Device Lifetime Green Organic Light Emitting Diodes using a Pt Complex. Issue 1 (25th September 2020) - Lee, Sunghun; Sim, Myung Sun; Kwak, Seung-Yeon; Koo, Hyun; Kim, Sangdong; Hong, SeokHwan; Hwang, Kyu Young; Yi, Jeoungin; Park, Sangho; Kwak, YoonHyun; Choi, Hyeonho; Lee, Bang Lin; et al.
Abstract : A High‐performance top‐emitting green phosphorescent OLED with a long operational lifetime, an LT of 200% longer and with a high current efficiency, 118% higher than the devices with state‐of‐the art Ir complexes at the luminance of 15, 000 cd m −2, was realized using a developed Pt complex and new hole transporting buffer and exciplex host materials. To the best of our knowledge, the current efficiency and lifetime of our achievements at this high luminance are more than 1.5 times higher and 100 times longer, respectively, than those of green phosphorescent OLEDs wit Pt complexes from literatures and materials companies in the world. This high current efficiency was achieved with higher horizontal transition dipole ratio, 86%, and short decay time, 2.4 μs, of our own developed Pt complex.